Effect of high salt concentration on phosphorus recovery from sewage sludge and dewatering properties. (October 2017) - Remmen, Kirsten; Niewersch, Claudia; Wintgens, Thomas; Yüce, Süleyman; Wessling, Matthias
Abstract: Phosphorus is an essential element in the life cycle of all organisms. Phosphorus rock is mined to produce fertilizers which are necessary to gain high crop yields. Phosphorus rock is limited, predictions of experts vary between 60 and 300 years availability of mineral deposits. A high phosphorus level in water bodies leads to eutrophication which is not only harmful to aquatic ecosystems but can also be a hazard for humans. Sewage sludge in wastewater treatment plants acts as a phosphorus sink and hence represents a promising source for phosphorus recovery. This paper is a study on the influence of high salinity waters on the dissolved phosphorus content in the liquid phase of waste activated sludge. Next to the dissolution effectiveness as a function of the sodium chloride concentration, the influence of the salt dose on the dewaterability is investigated. It is demonstrated that it is possible to increase the phosphorus content in the liquid phase by high salinity. Furthermore the sludge structure is changed which is beneficial for dewatering processes. In fact, dosing of salt can enhance phosphorus recovery efficiently in cases in which brines or residual salt is available close by wastewater treatment facilities.